Syndecan-4-dependent signaling in the inhibition of endotoxin-induced endothelial adherence of neutrophils by antithrombin - Kaneider, Nicole C.; Förster, Ellen; Mosheimer, Birgit; Sturn, Daniel H.; Wiedermann, Christian J. (Thrombosis and Haemostasis, 2003)
Circulating endotoxin is elevated in sepsis and plays a role in endothelial dysfunction whereas antithrombin is decreased by virtue of its consumption during complex formation with clotting factors and by proteolytic degradation by granulocyte elastase. Dysfunction of endothelium results in enhanced leukocyte rolling and diapedesis into tissues leading to edema formation and injury. Antithrombin exerts beneficial effects on endothelial function in sepsis. A direct anti-inflammatory action of anti-thrombin in inflammatory cells is exerted via heparan sulfate proteoglycans. In this study, we investigated whether antithrom-bin affects endotoxin-induced adhesion of neutrophils to human endothelial cells in vitro and whether glycosaminoglycans are involved in its signaling. Adhesion of human neutrophils to monolayers of umbilical vein endothelial cells was tested under static conditions. Endothelial cells were pretreated with endotoxin, interleukin-1, heparinase-I, chondroitinase-ABC or anti-syndecan-4-antibody. Endotoxin and interleukin-1 increased neutrophil adherence to human umbilical vein endothelial cells which was inhibited by antithrombin. Concomitant incubation with pentasaccharide abolished this effect of antithrombin. Treatment of endothelial cells with heparinase or chondroitinase led to higher adhesion and prevented effects of antithrom-bin. With antibodies to syndecan-4, enhanced adhesion of neutrophils was observed. As studied by Western blotting, endo-toxin-induced signaling was diminished by antithrombin and the effect was reversible by chondroitinase or heparinase. From our results, we can conclude that endotoxin-induced adhesion of leukocytes to endothelium can be reversed by ligation of syndecan-4 with antithrombin´s heparin-binding site and interferences with stress response signaling events in endothelium.
Keywords: Syndecan-4; neutrophils; antithrombin